Temporal variation in Sindbis virus antibody prevalence in bird hosts in an endemic area in Sweden - Hesson, Jenny Christina; Lundström, Jan O.; Tok, Atalay; Östman, Örjan; Lundkvist, Åke (PLOS ONE, 2016)
Sindbis virus (SINV) is a mosquito-borne bird virus that occasionally causes human disease in Fennoscandia, suggested to have cyclic 7-year intervals between outbreaks. Reliable data on human infections in Sweden is however lacking. Here we investigated the SINV antibody prevalence among birds in a Swedish area endemic to SINV to scrutinize if a cyclic variation in antibody prevalence is present in the natural host of SINV. Serum from birds were sampled in the summers of 2002-2004 and 2009 in the floodplains of the River Dalälven in central Sweden, with 2002 and 2009 representing hypothesized years of SINV outbreaks. A total of 963 birds from 52 species (mainly passerines) were tested for the presence of SINV antibodies using a plaque reduction neutralization test. The highest SINV antibody prevalence was found in Turdidae species, specifically Fieldfare, Redwing and Song thrush in which more than 70% of sampled individuals had antibodies to SINV in 2009. The SINV antibody prevalence significantly varied between years with 2% in 2002, 8% in 2003, 14% in 2004 and 37% in 2009. Antibodies were found equally often in hatchlings and in adults and increased from early to late in the season. Clearly, the SINV antibody prevalence was not elevated in the bird hosts in the predicted outbreak year 2002, thus solid evidence of a cyclic occurrence of SINV in Sweden is still lacking.